Rapid densification method for ceramic-based composite material

By covering amorphous carbon on the surface of ultra-high temperature nano powder and densification through RMI, the problem of long coating period and poor uniformity in the existing process is solved, and rapid densification and performance improvement of ceramic matrix composite materials are achieved. .

CN119462174APending Publication Date: 2025-02-18SDIC CERAMIC MATRIX COMPOSITES RES INST (XIAN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411426267.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

After impregnating ultra-high temperature ceramic particles, the existing process coats the ultra-high temperature ceramic particles by CVI-C or PIP-C, which has the problem of long periods and difficult to guarantee the uniformity of the coating.

Method used

A single-step in-situ polymerization method is used to coat the surface of ultra-high temperature nano powders with an amorphous carbon source. By adding organic carbon sources to the Tris buffer with pH 7.0 to 9.0, mixing and stirring evenly with the ultra-high temperature nano powders, centrifugation and Dry and then carbonized in a vacuum furnace to obtain a carbon-coated ultra-high temperature nanopowder, and the ceramic matrix composite material is further densified by RMI.

Benefits of technology

The rapid densification of ceramic matrix composite materials is achieved, and the density is increased from the initial 1.9g/cm3 to 2.3g/cm3, which improves the mechanical properties and ablation resistance of the material, while simplifying the process flow and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462174A_ABST
    Figure CN119462174A_ABST
Patent Text Reader

Abstract

The invention relates to preparation of a ceramic-based composite material, in particular to a rapid densification method of a ceramic-based composite material, which is used for overcoming the defects that in the prior art, after being impregnated, ultrahigh-temperature ceramic particles are coated by combining CVI-C or PIP-C, the cycle time is long, and the coating uniformity is difficult to guarantee. According to the rapid densification method for the ceramic-based composite material, a layer of amorphous carbon is coated on the surface of ultra-high-temperature nano-powder by adopting a one-step in-situ polymerization method, and the uniform carbon coating layer is beneficial to improving the wetting power of the ultra-high-temperature nano-powder during RMI, so that the RMI process effect of the ceramic-based composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of a ceramic-based composite material, and in particular to a rapid densification method for a ceramic-based composite material. Background Art

[0002] Ultra-High Temperature Ceramics (UHTCs) have become a class of materials with great application potential in the field of high-temperature materials due to their excellent high-temperature resistance, oxidation resistance and corrosion resistance. UHTCs represented by ZrC, HfC, TaC and HfB2 have performed well in aerospace, defense and energy fields. These materials are usually used to manufacture components with extremely high high-temperature performance requirements, such as the leading edge of space shuttles, missile tips and hypersonic vehicles.

[0003] In recent years, a large number of studies have shown that the introduction of UHTCs into ceramic matrix composites can significantly improve the material's resistance to ablation and oxidation. However, due to their respective advantages and disadvantages, it is difficult for a single process to effectively achieve UHTCs modification and densification of composite materials. Therefore, combined processes are widely used in the preparation of UHTCs-modified ceramic matrix composites. For example, commonly used combined processes include SI / RMI (solution impregnation / reactive melt impregnation), CVI / RMI (chemical vapor infiltration / reactive melt impregnation), Sol-gel / RMI (sol-gel / reactive melt impregnation) and CVI / PIP / RMI (chemical vapor infiltration / polymer impregnation pyrolysis / reactive melt impregnation).

[0004] Among these processes, RMI is considered to be a highly promising industrial production technology due to its advantages such as simple process, low cost, short product densification cycle and low residual porosity. However, in the existing process, after impregnating ultra-high temperature ceramic particles, ultra-high temperature ceramic particles are coated by combining CVI-C (chemical vapor infiltration carbonization) or PIP-C (polymer impregnation pyrolysis carbonization). There are problems such as long cycle time and difficulty in ensuring coating uniformity. The main reasons are: slow precursor penetration rate, irregularity of particle surface, complexity caused by multiple cycles, and stress and defect problems caused by high temperature process. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the existing process that, after impregnating ultra-high temperature ceramic particles, ultra-high temperature ceramic particles are coated by combining CVI-C or PIP-C, which has a long cycle time and is difficult to ensure coating uniformity, and to provide a method for rapid densification of ceramic-based composite materials.

[0006] In order to solve the deficiencies of the above-mentioned prior art, the present invention provides the following technical solutions:

[0007] A method for rapid densification of ceramic matrix composite materials, which is special in that it comprises the following steps:

[0008] Step 1, adding an organic carbon source to a Tris buffer having a pH value of 7.0 to 9.0, and mixing uniformly to obtain a solution A, wherein the mass ratio of the organic carbon source to the Tris buffer is 1:100 to 1:10;

[0009] Step 2: Mix the ultrahigh temperature nano powder with the solution A obtained in step 1, and stir evenly to obtain a solution B, wherein the mass ratio of the ultrahigh temperature nano powder to the solution A is 1:1 to 1:10;

[0010] The ultra-high temperature nano powder is one of HfC, ZrC and TaC, and has a particle size of 0.2 to 10 μm;

[0011] Step 3, centrifuging the solution B obtained in step 2, taking the precipitate and drying it, and then carbonizing it in a vacuum furnace to obtain a carbon-coated ultrahigh temperature nanopowder;

[0012] Step 4: Introduce the carbon-coated ultrahigh temperature nanopowder obtained in step 3 into the ceramic matrix composite material by slurry impregnation, and then further densify the ceramic matrix composite material by RMI to complete the rapid densification of the ceramic matrix composite material.

[0013] Furthermore, the step 3 is specifically as follows:

[0014] The solution B obtained in step 2 is centrifuged until the supernatant is colorless and transparent; then the bottom powder is dried at 50 to 150° C. for 10 to 40 hours to obtain an ultra-high temperature nano powder coated with organic carbon;

[0015] The organic carbon-coated ultrahigh temperature nano powder is carbonized in a vacuum furnace at a temperature of 500-1000° C., a heating rate of 1-10° C. / min, and a heat preservation time of 0.5-10 h to obtain the carbon-coated ultrahigh temperature nano powder.

[0016] Furthermore, the step 4 is specifically as follows:

[0017] The ceramic matrix material and the carbon-coated ultrahigh temperature nano powder are mixed, and a solvent is added and stirred to form a uniform slurry; then the porous ceramic matrix is ​​immersed in the slurry to allow the carbon-coated ultrahigh temperature nano powder in the slurry to penetrate into the pores of the porous ceramic matrix; after the impregnation is completed, the impregnated porous ceramic matrix is ​​taken out and dried to obtain a slurry-impregnated composite material; a molten metal or ceramic is introduced into the pores of the composite material and kept warm. After the reaction is completed, the temperature is slowly lowered to obtain a ceramic-based composite material, thereby completing the rapid densification of the ceramic-based composite material.

[0018] Furthermore, in step 2, the particle size of the ultra-high temperature nano powder is 1 to 3 μm.

[0019] Furthermore, in step 1, the mass ratio of the organic carbon source to the Tris buffer is 1:10;

[0020] In step 2, the mass ratio of the ultra-high temperature nano powder to solution A is 1:10, and the ultra-high temperature nano powder is HfC powder with a particle size of 2 μm.

[0021] Furthermore, in step 1, the pH value of the Tris buffer is 7.0.

[0022] Furthermore, in step 1, the mixing is uniformly carried out by: magnetic stirring for 1 to 3 hours;

[0023] In step 2, the uniform stirring specifically includes: magnetic stirring for 20 to 200 hours.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention discloses a method for rapidly densifying a ceramic-based composite material. The method uses a one-step in-situ polymerization method to coat a layer of amorphous carbon on the surface of an ultra-high temperature nanopowder. The uniform carbon coating layer is beneficial to improving the wetting dynamics of the ultra-high temperature nanopowder during RMI and enhancing the RMI process effect of the ceramic-based composite material. The obtained ceramic-based composite material has an initial density of 1.9 g / cm 3 , increased to 2.3 g / cm 3 , the effect of RMI is better than that of unmodified powder.

[0026] (2) The present invention can control the thickness of the carbon coating layer by adjusting the mass ratio of the organic carbon source to the Tris buffer and the temperature of the carbonization treatment, and can be adapted to ceramic-based composite materials of different types and pore structures for RMI process to achieve a rapid densification effect and improve their mechanical properties and anti-ablation properties.

[0027] (3) The present invention uses an organic carbon source as the raw material of the carbon coating layer, which has a wide range of sources and can greatly reduce the production cost of the product.

[0028] (4) Compared with other methods such as surface modification and modified grafting, the one-step in-situ polymerization method used in the present invention to coat organic carbon is simpler to operate and has higher preparation efficiency. The amorphous carbon obtained is more uniform on the surface of the ultra-high temperature nanopowder, and there is no other type of carbon impurities such as free carbon, which is beneficial to the subsequent RMI process of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a flow chart of steps 1 to 4 of Example 1 of a method for rapid densification of a ceramic-based composite material according to the present invention;

[0030] Figure 2 FTIR (Fourier transform infrared spectroscopy) spectrum in step 3.1 of Example 1 of the present invention;

[0031] Figure 3 This is the overall morphology of the carbon-coated HfC powder obtained by TEM (transmission electron microscopy) in step 3.2 of Example 1 of the present invention;

[0032] Figure 4 This is a high-resolution TEM image of the carbon-coated HfC powder obtained in step 3.2 of Example 1 of the present invention;

[0033] Figure 5 for Figure 4 The interface between HfC powder and carbon coating;

[0034] Figure 6 This is the mapping element distribution diagram of the carbon-coated HfC powder obtained in step 3.2 of Example 1 of the present invention;

[0035] Figure 7 This is a separate distribution diagram of carbon element in the carbon-coated HfC powder obtained in step 3.2 of Example 1 of the present invention;

[0036] Figure 8 This is a separate distribution diagram of the Hf (hafnium) element in the carbon coating obtained in step 3.2 of Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with the accompanying drawings and exemplary embodiments.

[0038] Embodiment 1

[0039] Reference Figure 1 , a method for rapid densification of ceramic matrix composite materials, comprising the following steps:

[0040] Step 1, adding an organic carbon source to a Tris buffer with a pH value of 7.0, and mixing well to obtain a solution A;

[0041] The preparation method of the Tris buffer is as follows:

[0042] Tris(hydroxymethyl)aminomethane (Tris, C4H 11 NO3) and tris(hydroxymethylaminomethane) hydrochloride (Tris-HCl, C4H 11 NO3·HCl) was dissolved in 10-100 ml of deionized water and stirred magnetically for 1-2 h to obtain Tris buffer;

[0043] In other embodiments, the mass ratio of tris(hydroxymethyl)aminomethane to tris(hydroxymethyl)aminomethane hydrochloride is 0.1-10:1, and the pH value of the Trils buffer is 7.0-9.0;

[0044] The organic carbon source is dopamine (Dopamine, C8H 11 NO2), in other embodiments, the organic carbon source may also be one of glucose, fatty acids, amino acids, fructose, and starch;

[0045] The mass ratio of the organic carbon source to the Tris buffer is 1:10. In other embodiments, the mass ratio of the organic carbon source to the Tris buffer may be 1:100 to 1:10. The mass ratio of the organic carbon source to the Tris buffer may affect the uniformity and thickness of the organic carbon coating on the surface of the ultra-high temperature nanopowder. Less organic carbon source may result in a too thin carbon coating layer, which cannot provide effective protection. More organic carbon source may result in excessive carbon deposition, which may affect subsequent sintering and composite material performance. At the same time, too much organic carbon source may affect the viscosity of solution A, thereby affecting its mixing uniformity with the ultra-high temperature nanopowder and affecting the final coating effect.

[0046] Step 2, mixing the ultrahigh temperature nano powder with the solution A obtained in step 1 at a mass ratio of 1:10, and magnetically stirring for 50 hours to obtain solution B;

[0047] The ultra-high temperature nano powder uses HfC powder with a particle size of 2 μm; in other embodiments, the ultra-high temperature nano powder may also use ZrC or TaC with a particle size of 0.2 to 10 μm; the smaller the particle size of the ultra-high temperature nano powder, the higher the reactivity, density and mechanical properties of the material, but at the same time it also increases the processing difficulty and agglomeration tendency;

[0048] In other embodiments, the mass ratio of the ultra-high temperature nano powder to the solution A may be 1:1 to 1:10. The mass ratio of the ultra-high temperature nano powder to the solution A may affect the adsorption and coating of the organic carbon source on the ultra-high temperature nano powder; if the mass ratio of the ultra-high temperature nano powder is too large, the organic carbon source in the solution may be insufficient, resulting in that part of the ultra-high temperature nano powder cannot be fully coated; if the mass ratio of the ultra-high temperature nano powder is too small, there will be too much carbon source remaining, wasting materials;

[0049] Step 3, centrifuging the solution B obtained in step 2, taking the precipitate and drying it, and then carbonizing it in a vacuum furnace to obtain a carbon-coated ultrahigh temperature nanopowder;

[0050] Step 3.1, centrifuging the solution B obtained in step 2 until the supernatant is colorless and transparent; then drying the bottom powder at 150° C. for 40 h to obtain organic carbon-coated HfC powder;

[0051] The centrifugation is performed by centrifugation and washing with alcohol and deionized water for 2 to 5 times respectively;

[0052] The drying temperature directly affects the formation of the organic carbon coating layer. The temperature is controlled between 50 and 150 °C to ensure that the organic carbon source is evenly distributed and forms a stable coating layer. If the temperature is too low, the drying is incomplete, which may cause residual solvents or impurities in the organic carbon coating layer to affect subsequent treatment. If the temperature is too high, the organic carbon source may decompose prematurely during the drying process, resulting in damage to the organic carbon coating layer.

[0053] FTIR was used to characterize the organic carbon-coated HfC powder. Figure 2 As shown, 3630~3846cm -1 The peaks between represent the stretching vibration peaks of OH or NH; 2949.1cm -1 The peak at 2949.1cm represents the CH stretching vibration peak on the saturated carbon; -1 The peak represents the CH stretching vibration peak in -CH2; the peak position is about 1558.4cm -1 The peak at 1276.88 cm represents the C=C / C=N / N=O stretching vibration peak in dopamine; -1 and 1496.76cm -1 The peak at 1045.4 cm corresponds to the stretching and bending vibrations of the COH bond in dopamine; -1 The peaks at 970.19 cm represent the CH in-plane bending vibration and CO stretching vibration peaks; -1 The peak represents the out-of-plane bending vibration of CH; the peak position is about 555.49cm -1 、669.29cm -1 The peak represents the torsional vibration peak of the benzene ring, indicating that polydopamine has been successfully coated on the surface of HfC powder;

[0054] Step 3.2, the organic carbon-coated HfC powder obtained in step 3 is carbonized in a vacuum furnace at a temperature of 1000°C and a heating rate of 10°C / min to prevent the organic carbon-coated HfC powder from cracking or deforming due to thermal stress during rapid heating. The holding time is 10 hours to ensure that the organic carbon source is fully converted into a carbon coating layer, and finally a carbon-coated HfC powder is obtained;

[0055] The carbon-coated HfC powder was characterized by TEM. Figures 3 to 8As shown, the thickness of the carbon coating layer on the surface of HfC powder was tested and counted by Nano Measurer statistical software, which was between 70 and 170 nm. Dopamine was completely coated on the surface of HfC powder by self-polymerization reaction. After coating, the carbon coating layer and HfC powder were clearly separated, and the outer shell showed obvious amorphous disordered state without other lattice stripes, which also showed that the carbon coating layer was amorphous carbon. The HfC powder and the carbon coating layer were analyzed by Mapping elements respectively, and the amorphous carbon was evenly distributed on the surface of HfC particles, which further showed that the dopamine carbon was evenly coated on the surface of HfC powder.

[0056] Step 4: Introduce the carbon-coated HfC powder obtained in step 3.2 into the ceramic matrix composite material by slurry impregnation, further densify the ceramic matrix composite material by RMI, and complete the rapid densification of the ceramic matrix composite material, as follows:

[0057] Step 4.1, mixing the ceramic matrix material and the carbon-coated HfC powder in an appropriate ratio, adding a solvent and stirring to form a uniform slurry;

[0058] Step 4.2, immersing the porous ceramic substrate into the slurry of step 4.1, so that the carbon-coated HfC powder in the slurry penetrates into the pores of the porous ceramic substrate;

[0059] Step 4.3, after the impregnation is completed, the impregnated porous ceramic substrate is taken out and dried at room temperature or in an oven to obtain a slurry-impregnated composite material;

[0060] Step 4.4, introducing the molten metal or ceramic into the pores of the composite material, and keeping the temperature for 0.5 to 10 hours; after the reaction is completed, slowly cooling down to obtain a ceramic-based composite material.

[0061] Embodiment 2

[0062] A method for rapid densification of ceramic-based composite materials comprises the following steps:

[0063] Step 1, adding an organic carbon source to a Tris buffer with a pH value of 8.0, and mixing well to obtain a solution A;

[0064] The organic carbon source is dopamine, and the mass ratio of the organic carbon source to the Tris buffer is 1:20;

[0065] Step 2, mixing the ultrahigh temperature nano powder with the solution A obtained in step 1 at a mass ratio of 1:3, and magnetically stirring for 50 hours to obtain solution B;

[0066] Ultra-high temperature nano powder uses ZrC powder with a particle size of 3μm;

[0067] Step 3.1, centrifuging the solution B obtained in step 2 until the supernatant is colorless and transparent; then drying the bottom powder at 100° C. for 40 hours to obtain organic carbon-coated ZrC powder;

[0068] Step 3.2, the organic carbon-coated ZrC powder obtained in step 3.1 is carbonized in a vacuum furnace at a temperature of 700°C and a heating rate of 5°C / min to prevent the organic carbon-coated ZrC powder from cracking or deforming due to thermal stress during rapid heating. The holding time is 5 hours to ensure that the organic carbon source is fully converted into a carbon coating layer, and finally a carbon-coated ZrC powder is obtained;

[0069] Step 4, introducing the carbon-coated ZrC powder obtained in step 3.2 into the ceramic matrix composite material by slurry impregnation, further densifying the ceramic matrix composite material by RMI, and completing the rapid densification of the ceramic matrix composite material;

[0070] The rest of the configuration of this embodiment is the same as that of the first embodiment.

[0071] Embodiment 3

[0072] A method for rapid densification of ceramic-based composite materials comprises the following steps:

[0073] Step 1, adding an organic carbon source to a Tris buffer with a pH value of 8.0, and mixing well to obtain a solution A;

[0074] The organic carbon source is dopamine, and the mass ratio of the organic carbon source to the Tris buffer is 1:100;

[0075] Step 2: Mix the ultrahigh temperature nano powder with the solution A obtained in step 1 at a mass ratio of 1:1, and stir magnetically for 50 hours to obtain solution B;

[0076] The ultra-high temperature nano powder uses TaC powder with a particle size of 1μm;

[0077] Step 3.1, centrifuging the solution B obtained in step 2 until the supernatant is colorless and transparent; then drying the bottom powder at 50° C. for 40 h to obtain organic carbon-coated TaC powder;

[0078] Step 3.2, the organic carbon-coated TaC powder obtained in step 3.1 is carbonized in a vacuum furnace at a temperature of 500°C and a heating rate of 1°C / min to prevent the organic carbon-coated TaC powder from cracking or deforming due to thermal stress during rapid heating. The holding time is 0.5h to ensure that the organic carbon source is fully converted into a carbon coating layer, and finally a carbon-coated TaC powder is obtained;

[0079] Step 4, introducing the carbon-coated TaC powder obtained in step 3.2 into the ceramic matrix composite material by slurry impregnation, further densifying the ceramic matrix composite material by RMI, and completing the rapid densification of the ceramic matrix composite material;

[0080] The rest of the configuration of this embodiment is the same as that of the first embodiment.

Claims

1. A method for rapid densification of ceramic-based composite materials, characterized in that: The steps include: Step 1, adding an organic carbon source to a Tris buffer having a pH value of 7.0 to 9.0, and mixing uniformly to obtain a solution A, wherein the mass ratio of the organic carbon source to the Tris buffer is 1:100 to 1:10; Step 2: Mix the ultrahigh temperature nano powder with the solution A obtained in step 1, and stir evenly to obtain a solution B, wherein the mass ratio of the ultrahigh temperature nano powder to the solution A is 1:1 to 1:10; The ultra-high temperature nano powder is one of HfC, ZrC and TaC, and has a particle size of 0.2 to 10 μm; Step 3, centrifuging the solution B obtained in step 2, taking the precipitate and drying it, and then carbonizing it in a vacuum furnace to obtain a carbon-coated ultrahigh temperature nanopowder; Step 4: Introduce the carbon-coated ultrahigh temperature nanopowder obtained in step 3 into the ceramic matrix composite material by slurry impregnation, and then further densify the ceramic matrix composite material by RMI to complete the rapid densification of the ceramic matrix composite material.

2. A method for rapid densification of ceramic matrix composite materials according to claim 1, characterized in that: The step 3 is specifically as follows: The solution B obtained in step 2 is centrifuged until the supernatant is colorless and transparent; then the bottom powder is dried at 50 to 150° C. for 10 to 40 hours to obtain an ultra-high temperature nano powder coated with organic carbon; The organic carbon-coated ultrahigh temperature nano powder is carbonized in a vacuum furnace at a temperature of 500-1000° C., a heating rate of 1-10° C. / min, and a heat preservation time of 0.5-10 h to obtain the carbon-coated ultrahigh temperature nano powder.

3. A method for rapid densification of ceramic matrix composite materials according to claim 2, characterized in that: The step 4 is specifically as follows: The ceramic matrix material and the carbon-coated ultrahigh temperature nano powder are mixed, and a solvent is added and stirred to form a uniform slurry; then the porous ceramic matrix is ​​immersed in the slurry to allow the carbon-coated ultrahigh temperature nano powder in the slurry to penetrate into the pores of the porous ceramic matrix; after the impregnation is completed, the impregnated porous ceramic matrix is ​​taken out and dried to obtain a slurry-impregnated composite material; a molten metal or ceramic is introduced into the pores of the composite material and kept warm. After the reaction is completed, the temperature is slowly lowered to obtain a ceramic-based composite material, thereby completing the rapid densification of the ceramic-based composite material.

4. A method for rapid densification of a ceramic matrix composite material according to any one of claims 1 to 3, characterized in that: In step 2, the particle size of the ultra-high temperature nano powder is 1 to 3 μm.

5. A method for rapid densification of a ceramic matrix composite material according to claim 4, characterized in that: In step 1, the mass ratio of the organic carbon source to the Tris buffer is 1:10; In step 2, the mass ratio of the ultra-high temperature nano powder to solution A is 1:10, and the ultra-high temperature nano powder is HfC powder with a particle size of 2 μm.

6. A method for rapid densification of a ceramic matrix composite material according to claim 4, characterized in that: In step 1, the pH value of the Tris buffer is 7.

0.

7. A method for rapid densification of a ceramic matrix composite material according to claim 4, characterized in that: In step 1, the mixing is uniformly carried out by: magnetic stirring for 1 to 3 hours; In step 2, the uniform stirring specifically includes: magnetic stirring for 20 to 200 hours.

Citation Information

Patent Citations

  • Method for preparing silicon nitride ceramic with low oxygen content and high thermal conductivity by carbon coating and application of silicon nitride ceramic

    CN111875387A

  • Preparation method of fiber toughened ceramic-based composite material

    CN117964380A